Encyclopedia of Herbal Medicine - Andrew Chevallier (Dorling Kindersley Ltd, 2016)
Are you using natural remedies to reduce stress or improve your health? With the fully updated and revised Encyclopedia of Herbal Medicine, you can join the ever-increasing numbers that are. Written by Andrew Chevallier, a fellow of the National Institute of Medical Herbalists, the Encyclopedia of Herbal Medicine is the unrivalled guide to home healing and herbal medicine. With entries showcasing 550 medicinal herbs including aloe vera, sage, and nettle, and nearly 200 remedy lists, you can learn how to treat a wide variety of common ailments from the comfort of your own home. The Encyclopedia of Herbal Medicine details the properties of each medicinal herb, with a strong focus on safety to ensure safe natural healing for the whole family. Learn how to grow, harvest, and process your own ingredients to create natural remedies and improve your health - naturally.